Color stability of ceramic brackets immersed in potentially staining solutions - Guignone, Bruna Coser; Silva, Ludimila Karsbergen; Soares, Rodrigo Villamarim; Akaki, Emilio; Goiato, Marcelo Coelho [UNESP]; Pithon, Matheus Melo; Oliveira, Dauro Douglas (FapUNIFESP (SciELO), 2015)
Objective: To assess the color stability of five types of ceramic brackets after immersion in potentially staining solutions. Methods: Ninety brackets were divided into 5 groups (n = 18) according to brackets commercial brands and the solutions in which they were immersed (coffee, red wine, coke and artificial saliva). The brackets assessed were Transcend (3M/ Unitek, Monrovia, CA, USA), Radiance (American Orthodontics, Sheboygan, WI, USA), Mystique (GAC International Inc., Bohemia, NY, USA) and Luxi II (Rocky Mountain Orthodontics, Denver, CO, USA). Chromatic changes were analyzed with the aid of a reflectance spectrophotometer and by visual inspection at five specific time intervals. Assessment periods were as received from the manufacturer (T0), 24 hours (T1), 72 hours (T2), as well as 7 days (T3) and 14 days (T4) of immersion in the aforementioned solutions. Results were submitted to statistical analysis with ANOVA and Bonferroni correction, as well as to a multivariate profile analysis for independent and paired samples with significance level set at 5%. Results: The duration of the immersion period influenced color alteration of all tested brackets, even though these changes could not always be visually observed. Different behaviors were observed for each immersion solution; however, brackets immersed in one solution progressed similarly despite minor variations. Conclusions: Staining became more intense over time and all brackets underwent color alterations when immersed in the aforementioned solutions.
Keywords: Color instability; Optical properties; Orthodontic brackets